Pengaruh Risiko Audit dan Fee Audit Terhadap Kualitas Audit dengan Pengalaman Kerja Sebagai Moderasi (Studi Kasus Pada Kantor Akuntan Publik Malang) - Kumalasari, Dwi; Mahsuni, Abdul Wahid; Mawardi, M. Cholid (Universitas Islam Malang, 2024)
This study aims to analyze the effect of audit risk and audit fees on audit quality with work experience as moderation. This research is a quantitative research with an associative approach using primary data obtained from questionnaires and measured using the Likert Scale. The data analysis method used is multiple linear regression analysis processed using SEM-PLS. The population in this study is Auditors who are still actively working in Malang Public Accountants with 12 samples of Malang Public Accountants. Data was collected from 55 respondents through questionnaires given to the Malang City Public Accountant Auditor, using purposive sampling techniques. The results of the analysis show that Audit Risk and Work Experience have a significant positive effect on Audit Quality, while Audit Fee does not affect Audit Quality. Work Experience have an effect moderating Audit Risk on Audit Quality while Work Experience does not play a role in moderating Audit Fees on Audit Quality.Keywords: Audit risk, audit fee, work experience, audit quality.